Coagulation Factor XII Gene Mutation in Brazilian Families with Hereditary Angioedema with Normal C1 Inhibitor - Moreno, Adriana S.; Valle, Solange O. R.; Levy, Soloni; Franca, Alfeu T.; Serpa, Faradiba S.; Arcuri, Helen A.; Palma, Mario S. [UNESP]; Campos, Wagner N.; Dias, Marina M.; Ponard, Denise; Monnier, Nicole; Lunardi, Joel; et al. (Karger, 2015)
Background: Hereditary angioedema (HAE) with normal C1 inhibitor (C1-INH) is a rare disorder. Mutations of the gene encoding coagulation factor XII have been identified in a subset of patients with this condition. Our aim was to investigate mutations in the F12 gene in patients with HAE with normal C1-INH from Brazil. Methods: We studied 5 Brazilian families with index female patients who presented with recurrent angioedema with normal C1-INH and C4 levels. Genomic DNA was isolated from whole blood and PCR was performed. Mutations were detected by the sequencing of exon 9 of the F12 gene and allelic discrimination. Results: The c.983C>A (p.Thr328Lys) mutation was identified in 16 subjects, from 4 of the 5 families studied, including 8 patients with symptoms of HAE with normal C1-INH (87.5% women) and 8 subjects asymptomatic for HAE (25% women). Mean age at onset of symptoms among the FXII-HAE patients was 13.8 years (range 6-25 years). Recurrent abdominal pain (100%) and subcutaneous angioedema (87.5%) were the most frequent clinical presentations. Two patients presented with associated laryngeal edema. In keeping with previous observations in patients with both C1-INH-HAE and HAE with normal C1-INH, all 7 women with FXII-HAE reported triggering or worsening of symptoms upon intake of estrogen-containing oral contraceptives and/or pregnancy. Conclusions: We report for the first time in Brazil a mutation in the F12 gene as a likely cause of HAE with normal C1-INH in patients with recurrent attacks of angioedema and/or abdominal pain. A higher frequency of abdominal pain attacks and onset of symptoms at a younger age were observed among Brazilian patients when compared to those from other parts of the world. (C) 2015 S. Karger AG, Basel
Keywords: Hereditary angioedema; Coagulation factor XII; C1 inhibitor